The Impact of Inherited Morphology on Sandbar Migration During Mild Wave Seasons. Issue 3 (2nd February 2023) - Anderson, Dylan; Bak, A. Spicer; Cohn, Nicholas; Brodie, Katherine L.; Johnson, Bradley; Dickhudt, Patrick
Abstract: Sandbars are ubiquitous morphologic features found in the nearshore environment throughout the world, yet predictive capabilities of their evolution remain limited. In order to provide new insights on the relevant processes controlling sandbar morphodynamics, this study uses a 41‐year record of 637 monthly cross‐shore profiles from Duck, North Carolina, USA, to derive complex empirical orthogonal functions representative of the two dominant modes of sandbar migrations: offshore and onshore propagation. Interference of these two modes produces commonly observed sandbar states. While mild wave energies are traditionally assumed to drive onshore sandbar migration, the offshore mode is repeatedly seen to dominate sandbar migration in mild wave seasons following anomalously high late‐winter wave energy and when the inherited morphology is composed of a single bar or terrace, as opposed to a more common two‐bar state. A data‐derived conceptual model is presented synthesizing the effect of antecedent morphology and wave climate chronology on interannual trends in net offshore sandbar migration. Plain Language Summary: Sandbars commonly exist in shallow water just offshore of sandy coastal beaches. These features are thought to play an important role in protecting the beach from storm waves, but unfortunately there is limited skill in predicting how these sandbars form and move. An unparalleled 41‐year, monthly data set of nearshore sandbar behavior is used in this work to identify a repetitive pattern where emergence of new sandbars in the nearshore occurs when offshore migration occurs during mild wave seasons, which is contradictory to traditional conceptual models for nearshore morphology evolution. A new conceptual map is derived from the data that identifies common sandbar states and the migration direction that produces changes from one state to another, specifically highlighting that sandbar migration direction at the seasonal to yearly scale is strongly dependent on winter wave climates and the sandbar state at the beginning of mild wave seasons each spring. Key Points: Sandbar migrations in on‐ and offshore directions expressed as propagating modes derived from 41 years of surveys Offshore migrations are observed during mild wave conditions when a single‐bar or terraced beach profile is present The relative timing of large wave energy prior to extended periods of mild conditions enables offshore migrations